An exploration of a weight management programme for pregnant women living with obesity - Ellis, Sarah (2023)
Introduction: Pregnancy is a time of both transformation and adaptation within the human body. Entering pregnancy with a body mass index (BMI) above the healthy range of 18.5-24.9kg/m2 increases a range of health risks for both the mother and baby and so is a targeted area for weight management. This thesis aims to evaluate a weight management programme (Bumps and Beyond) developed for pregnant women with a high BMI and delivered in two geographic areas in the UK. Methods: Service evaluation was based on audit sheets completed by staff at the two locations. Data from anonymised records were statistically analysed to see if the intervention reduced gestational weight gain, and complications in pregnancy and labour. Intervention fidelity was reviewed via transcripts of staff delivering the intervention in Lincolnshire. Hermeneutic phenomenological analysis (HPA) was undertaken on transcripts of staff delivering the sessions within the intervention at one site. The HPA used the novel approach of utilising the Roles of ‘Sarah the Mother’, ‘Sarah the Dietitian’, and ‘Sarah the Researcher’ to find the essence within the texts of the transcripts. Results: Intervention fidelity was good, and staff were responsive to participants' needs. Full attendance at Lincolnshire Bumps and Beyond showed a positive impact on gestational weight gain, total pregnancy complications, pre-eclampsia, preterm birth, low birth weight and breastfeeding initiation. Full attendance at Nottinghamshire Bumps and Beyond did not show the same benefits and was associated with greater risk of instrumental delivery and lower breastfeeding initiation. HPA of transcripts brought out several essences for each role that indicated possible pathways for development of the programme in the future. Discussion: The contrasting efficacy of Bumps and Beyond at the two locations gives a clear indication that just transferring a programme from one setting to another is not enough to ensure it will be successful. Despite being geographically close, the two locations had different populations which may in part explain the lack of success in Nottinghamshire. In addition to this, the type of staff may have had some effect in how the programme was delivered in each location. Use of the HPA output allowed insight into possible areas that could be further developed or adapted for the population the intervention is to serve. The Bumps and Beyond programme is similar to other small-scale midwife-led interventions that report positive outcomes in one local area. Larger trials have been less successful overall. Conclusion: Small local interventions to control gestational weight gain in women living with obesity can be effective when adapted to suit the needs of the population.